Hereditary Spastic Paraplegia: Clinical Principles and Genetic Advances - Fink, John K. (Seminars in Neurology, 2014)
Hereditary spastic paraplegia (HSP) refers to inherited disorders in which spastic gait is either the only feature or is a major syndrome feature. There are more than 70 genetic types of HSP. Neuropathological studies, albeit limited to only a few genetic types of HSP, have identified axon degeneration involving the distal ends of the corticospinal tracts and fasciculus gracilis fibers. In this review, the author highlights the clinical and genetic features of HSP.
Keywords: spastic paraplegia; hereditary; spinal cord; genetic